Effects Of Interactive E-Books In Enhancing Mandarin Language Vocabulary Acquisition, Story Comprehension And Story Retelling Among Kindergarten Children In China - Chen, Chuang (2024)
In today's digital age, where children increasingly devote a significant part of their reading activities to screens, researchers are increasingly focused on understanding the effects of using interactive e-books in children's reading experiences. This study investigated the effects of high-, low-, and non-interactivity levels of e-books on promoting mandarin vocabulary acquisition, story comprehension, and story retelling among chinese kindergarten children, with gender as a moderator variable. Guided by the cognitive theory of multimedia learning (ctml), the cognitive-affective theory of learning with media (catlm), and cognitive load theory (clt), a posttest-only control group experimental research design was conducted to evaluate the effects of these different e-book formats. The sample consisted of 90 children (45 boys and 45 girls) from a public kindergarten in zhengzhou city, henan province, china. This study used one-way analysis of variance (anova) with post hoc testing to identify differences between groups, and two-way analysis of variance (anova) to examine interaction effects between independent variables and moderator variables.